2017
DOI: 10.2147/ijwh.s103789
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional/four-dimensional transperineal ultrasound: clinical utility and future prospects

Abstract: During the last decade, there has been a huge advancement in the use of transperineal ultrasound (TPU) in the field of obstetrics and gynecology. Its main applications in obstetrics include the monitoring of fetal progression in labor and recently the assessment of maternal pelvic dimensions, whereas in gynecology, TPU is at present widely used for the evaluation of the female pelvic floor, opening new boundaries for the assessment of pelvic floor disorders. The association of volumetric three-dimensional tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 87 publications
0
26
0
1
Order By: Relevance
“…LAM avulsion is an important risk factor for POP, and it has been suggested to be the missing link between childbirth and POP . The 3D/4D TPU offers a reliable and accurate tool for the assessment of LAM integrity and function . The gold standard for the diagnosis of levator ani injuries remains the multislice technique (TUI) proposed by Dietz et al In most cases of LAM injury, qualitative evaluation is sufficient to diagnose or exclude the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…LAM avulsion is an important risk factor for POP, and it has been suggested to be the missing link between childbirth and POP . The 3D/4D TPU offers a reliable and accurate tool for the assessment of LAM integrity and function . The gold standard for the diagnosis of levator ani injuries remains the multislice technique (TUI) proposed by Dietz et al In most cases of LAM injury, qualitative evaluation is sufficient to diagnose or exclude the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high level of availability and the increasing dissemination of transperineal sonography, relevant measuring points at the transperineal image of the pelvic floor are still missing (the pubis is the one bony structure that retains the position during movement, such as Valsalva) [29,30]. This however leaves too much scope for interpretation.…”
Section: Materials and Methodmentioning
confidence: 99%
“…Many studies, both in obstetrics and gynecology, have demonstrated that TPU can provide valuable information for the clinician. In gynecology, TPU is a reliable and reproducible tool for static and dynamic assessment of pelvic floor morphology and biometry [1][2][3][4][5][6] . In addition to providing important information in urogynecological patients, TPU has considerably improved our understanding of the relationship between labor and pelvic floor disorders 2,3,[7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%